1999
DOI: 10.1093/clinchem/45.2.213
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Cardiac Troponin I Forms in the Blood of Patients with Acute Myocardial Infarction and Patients Receiving Crystalloid or Cold Blood Cardioplegia

Abstract: To determine the forms of cardiac troponin I (cTnI) circulating in the bloodstream of patients with acute myocardial infarction (AMI) and patients receiving a cardioplegia during heart surgery, we developed three immunoenzymatic sandwich assays. The first assay involves the combination of two monoclonal antibodies (mAbs) specific for human cTnI. The second assay involves the combination of a mAb specific for troponin C (TnC) and an anti-cTnI mAb. The third assay was a combination of a mAb specific for human ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(25 citation statements)
references
References 25 publications
1
22
0
2
Order By: Relevance
“…It is unlikely that cardiac troponin I crosses the placenta, given its molecular weight of 24,000 kd and the fact that it exists in the circulation predominantly as a binary complex. 12 No data exist describing placental production of cardiac troponin I, and its specificity for cardiac muscle, as distinct from vascular smooth muscle, would make this improbable. It therefore seems likely that the cardiac troponin I levels measured in this study are the result of endogenous fetal production.…”
Section: Discussionmentioning
confidence: 99%
“…It is unlikely that cardiac troponin I crosses the placenta, given its molecular weight of 24,000 kd and the fact that it exists in the circulation predominantly as a binary complex. 12 No data exist describing placental production of cardiac troponin I, and its specificity for cardiac muscle, as distinct from vascular smooth muscle, would make this improbable. It therefore seems likely that the cardiac troponin I levels measured in this study are the result of endogenous fetal production.…”
Section: Discussionmentioning
confidence: 99%
“…The maximal amount of free cTnI was released shortly after the injury. The presence of cTnI/ cTnT complex has also been demonstrated, 43 although in very small amounts. In blood, it is probable that the T/I/C complex dissociates with time into free cTnT and I/C complex.…”
Section: Cardiac Troponinsmentioning
confidence: 99%
“…Recent studies have found that in patients after AMI the predominant form of cTnI exhibited in blood is the binary troponin IC complex with slight concentrations of ternary ITC complex, binary IT complex and free cTnI [82][83][84][85]. The release pattern of these forms in MI is still under investigation.…”
Section: Cardiac Troponin Imentioning
confidence: 99%